Pengaruh Social Adjustive dan Harga Terhadap Niat Pembelian Produk Handbags Palsu - Musnaini Musnaini (STIE Malangkucecwara, 2014)
The objective of this study is to investigate factors of purchasing intentention on pirated products. That factors of attitude function caused consumers non-deceptive choose to buy counterfeit handbag. This study use Handbags Louis Vuitton(LV) scenario to stimulate, also brand as variable affected consumers purchased intention and perceived social value. Sales of pirated fashion products remain high despite various industry effortd to constrain the growth. Based on psychological theory, this study arggues that the rise of pirated fashion products such as handbags due some constraints in the supply side such as high price and consumers side such as social adjusted. The questioners spread to two hundred twenty one under graduate student at Economic Faculty Jambi University. Metode uses Experiment group-control group design and between subject with design factorial 2 (social adjusted: high and low) x 2 (price: high and low). To understand differences between treatmen group, use MANCOVA test. The result indicate that social adjusted and high price increase the favorability of purchasing pirated fashion product specialy as handbags of Louis Vuitton. The interaction among two variables is alsosignificant and indicated the low social adjusted and low price effective on reducing favorability of consumers on purchasing pirated Handbags of fashion product.